2011
DOI: 10.1007/s13762-011-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the individual and social rights condition of climate refugees from the international environmental law perspective

Abstract: In evaluating international treaties, in particular, the United Nations Framework on Climate Change Convention, this paper shows that necessary preparations have not been made to protect the rights of individuals who are refugees or have been forced to migrate from their homeland. Immigrants are deprived of the most essential human rights, such as language, culture, and having a right to a healthy living environment. The current legal administration has not made the necessary contingencies for responding to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In addition, Zeben (2013) improved a competence allocation approach for European environmental law by accounting economies of scale, regulated jurisdiction conditions, and heterogeneity of preferences. While Pourhashemi et al (2012) affirmed that the determination of international community's duties and commitments can improve the efficiency of current legal administration in responding to the environment-related immigration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Zeben (2013) improved a competence allocation approach for European environmental law by accounting economies of scale, regulated jurisdiction conditions, and heterogeneity of preferences. While Pourhashemi et al (2012) affirmed that the determination of international community's duties and commitments can improve the efficiency of current legal administration in responding to the environment-related immigration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Undoubtedly, the region of West Asia enjoys the blessings of natural resources: for example, vast arable lands, rivers and minerals, and so on. Africa is one of the most prosperous regions on the continent, but it is also home to extreme poverty, unimaginable misery, and unprecedented environmental degradation [20]. Environmental justice is a huge vacuum in rich regions like Africa, and it can be said that the African environment does not support environmental justice.…”
Section: Sustainable Development and Environmental Injusticementioning
confidence: 99%
“…The study's findings have shown three main focuses in order to protect such right; engaging, effectiveness, and efficiency. To a broader aspect, Pourhashemi et al [69] examined the international treaties and the United Nations Framework on Climate Change Convention in particular, as well as to evaluate the existing forms of legal and operational protection in relation with climate change. From this study, they have found many issues, and a failure to protect the rights of refugees and immigrants comes before hand.…”
Section: Literature Reviewmentioning
confidence: 99%